Prospective Evaluation of a Rapid Diagnostic Test Dot EIA (Typhidot) for Typhoid Fever - Haji Khan Khoharo; Shuaib Ansari; Fatima Qureshi (Journal of the Dow University of Health Sciences, 2009)
Objective: